Analysis of Performance Between Islamic and Conventional Stock Portfolios in Malaysia - Bin Maryani, Musthofa Ahmad; Bin Ismail, Isaudin (Enhanced Knowledge in Sciences and Technology, 2022)
There are differences in performance between Islamic and conventional stock market. Islamic market often gives lower return but lower volatility while the conventional market is often more risk and debt oriented but carry higher return. There are 10 portfolios that are assessed and divided into Islamic and conventional portfolios, which in turn divided into five sectors: consumer, industrial, property, energy, and transportation and logistics. To measure performance, Jensen’s alpha, Sharpe ratio and Treynor ratio are used. Beta is also used to measure volatility against Kuala Lumpur Composite Index (FBMKLCI). Linear Regression Model is used to forecast trend of the portfolio. Analysis found that among the stocks and its market sector there is no difference of volatility in most of the stocks, and the return of conventional portfolio is higher than its Islamic counterparts. The average Beta value is quite similar between the two main portfolios, albeit on different sectors. The forecast analysis shows that the number of Islamic portfolios that have more positive trend is higher than the conventional ones.